#TITLE_ALTERNATIVE# - (NIM 250 04 023), Caswin
Abstract: This thesis describes of developing mathematical model which use fiber section based on new constitutive model for concrete-filled steel tubular columns ( for next is called CFST columns), for analysis reinforced ratio to the behavior and to the strength of short CFST section column which is represented interaction diagram, moment-curvature and curvature ductility. The result of fiber analysis was verified to the reference program. Both of the analysis has the same result. The purpose of study case analysis was to know the influence of longitudinal reinforced ratio and grade of concrete cylinder to the strength and behavior of short CFST column section which was caused by nominal axial compression and nominal moment. Several conclusion have been established in this analysis result.